Androgens, Endometriosis and Pain - Evans, Susan F.; Hull, M. Louise; Hutchinson, Mark R.; Rolan, Paul E. (Frontiers in Reproductive Health, 2021)
The intriguing relationship between androgens, endometriosis and chronic pain continues to unfold. Determining this relationship is of crucial importance to gynecologists managing people with these conditions, as common treatments dramatically alter her hormonal profiles, with both intended and unintended consequences. Although they may be present in the same individual, there is a recognized disconnect between pain or pain-related symptoms, and the presence or extent of endometriosis lesions. Reduced androgen levels provide a potential mechanism to link the development of endometriosis lesions and the presence of chronic pain. This research paper expands the presentation of our research at the World Endometriosis Congress in 2021, subsequently published in the Journal of Pain Research which demonstrated a strong inverse relationship between androgen levels and days per month of pelvic and period pain. Here we extend and further explore the evidence for a role for androgens in the etiology and management of dysmenorrhea and pelvic pain in women, both with and without endometriosis. We explore the potential for inflammation to induce low androgen levels and consider ways in which clinicians can optimize levels of androgens when treating women with these conditions. This article prompts the question: Is it estrogens that predispose people to a life of pain, or androgens that are protective?